Brentuximab vedotin or physician's choice in CD30-positive cutaneous T-cell lymphoma (ALCANZA): an international, open-label, randomised, phase 3, multicentre trial. Issue 10094 (5th August 2017) - Prince, H Miles; Kim, Youn H; Horwitz, Steven M; Dummer, Reinhard; Scarisbrick, Julia; Quaglino, Pietro; Zinzani, Pier Luigi; Wolter, Pascal; Sanches, Jose A; Ortiz-Romero, Pablo L; Akilov, Oleg E; Geskin, Larisa; et al.
Summary: Background: Cutaneous T-cell lymphomas are rare, generally incurable, and associated with reduced quality of life. Present systemic therapies rarely provide reliable and durable responses. We aimed to assess efficacy and safety of brentuximab vedotin versus conventional therapy for previously treated patients with CD30-positive cutaneous T-cell lymphomas. Methods: In this international, open-label, randomised, phase 3, multicentre trial, we enrolled adult patients with CD30-positive mycosis fungoides or primary cutaneous anaplastic large-cell lymphoma who had been previously treated. Patients were enrolled across 52 centres in 13 countries. Patients were randomly assigned (1:1) centrally by an interactive voice and web response system to receive intravenous brentuximab vedotin 1·8 mg/kg once every 3 weeks, for up to 16 3-week cycles, or physician's choice (oral methotrexate 5–50 mg once per week or oral bexarotene 300 mg/m 2 once per day) for up to 48 weeks. The primary endpoint was the proportion of patients in the intention-to-treat population achieving an objective global response lasting at least 4 months per independent review facility. Safety analyses were done in all patients who received at least one dose of study drug. This trial was registered withClinicalTrials.gov, numberNCT01578499 . Findings: Between Aug 13, 2012, and July 31, 2015, 131 patients were enrolled and randomly assigned to a group (66 to brentuximab vedotin and 65 to physician's choice), with 128 analysed in the intention-to-treat population (64 in each group). At a median follow-up of 22·9 months (95% CI 18·4–26·1), the proportion of patients achieving an objective global response lasting at least 4 months was 56·3% (36 of 64 patients) with brentuximab vedotin versus 12·5% (eight of 64) with physician's choice, resulting in a between-group difference of 43·8% (95% CI 29·1–58·4; p<0·0001). Grade 3–4 adverse events were reported in 27 (41%) of 66 patients in the brentuximab vedotin group and 29 (47%) of 62 patients in the physician's choice group. Peripheral neuropathy was seen in 44 (67%) of 66 patients in the brentuximab vedotin group (n=21 grade 2, n=6 grade 3) and four (6%) of 62 patients in the physician's choice group. One of the four on-treatment deaths was deemed by the investigator to be treatment-related in the brentuximab vedotin group; no on-treatment deaths were reported in the physician's choice group. Interpretation: Significant improvement in objective response lasting at least 4 months was seen with brentuximab vedotin versus physician's choice of methotrexate or bexarotene. Funding: Millennium Pharmaceuticals Inc (a wholly owned subsidiary of Takeda Pharmaceutical Company Ltd), Seattle Genetics Inc.